2022
DOI: 10.1155/2022/2584698
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Properties and Toxicological Assessment of Antidesma celebicum Miq: Ethanolic Leaves Extract in Sprague–Dawley Rats

Abstract: Antidesma is a genus of plants, and its several species are known to have antidiabetic properties. Leaves of Kayu Tuah (Antidesma celebicum Miq) have been proven to have the best α-glucosidase inhibition ability compared to other species in the Antidesma genus, as evidenced by the in vitro α-glucosidase inhibition test. However, no scientific studies have reported its antidiabetic properties and toxicity in vivo. Therefore, this research managed to verify the antidiabetic features and safety of ethanolic extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In addition, A. celebicum could normalize cholesterol, LDL, and triglyceride levels similar to acarbose treatment. 71 Previous studies indicated the effects of different Antidesma species on carbohydrate and lipid metabolism with respect to inhibition of digestive enzymes, lowering FBG and cholesterol/triglyceride levels, as well as modulating HDL/ LDL-cholesterol ratio in enzymatic and animal models. The pharmacological evidences partly explained the uses of Antidesma plants in herbal practices of treating indigestion, lack of appetite, and other metabolic problems.…”
Section: Effects On Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, A. celebicum could normalize cholesterol, LDL, and triglyceride levels similar to acarbose treatment. 71 Previous studies indicated the effects of different Antidesma species on carbohydrate and lipid metabolism with respect to inhibition of digestive enzymes, lowering FBG and cholesterol/triglyceride levels, as well as modulating HDL/ LDL-cholesterol ratio in enzymatic and animal models. The pharmacological evidences partly explained the uses of Antidesma plants in herbal practices of treating indigestion, lack of appetite, and other metabolic problems.…”
Section: Effects On Metabolismmentioning
confidence: 99%
“…In addition, A. celebicum could normalize cholesterol, LDL, and triglyceride levels similar to acarbose treatment. 71…”
Section: Pharmacological Studiesmentioning
confidence: 99%